Novel Application of Exhaled Carbon Monoxide Monitors: Smoking Cessation in Orthopaedic Trauma Patients. Issue 11 (November 2019) - Matuszewski, Paul E.; Comadoll, Shea M.; Costales, Timothy; Zerhusen, Timothy; Coale, Max; O'Toole, Robert V.
Abstract : Objectives: To determine whether an in-office exhaled carbon monoxide (CO) monitor can increase interest in smoking cessation among the orthopaedic trauma population. Design: Prospective. Setting: Level I trauma center. Patients: One hundred twenty-four orthopaedic trauma patients. Intervention: In-office measurement of exhaled CO. Main Outcome Measures: Stage of change, Likert scale score on willingness to quit today, patient's request for referral to a quitline, and increase in readiness to quit. Results: The use of an exhaled CO monitor increased willingness to quit in 71% of participants still smoking and increased willingness to quit on average by 0.8 points on a 10-point Likert scale ( P < 0.001). Fifteen percent of patients modified their stage of change toward quitting. Forty percent of patients after exhaled CO monitor requested referral to a quitline, compared with 4% presurvey ( P < 0.001). Anecdotally, most participants were very interested in the monitoring device and its reading, expressing concern with the result. The value of exhaled CO was not associated with any measured outcomes. Conclusions: The use of an exhaled CO monitor increased willingness to quit smoking in 71% of patients, but the effect size was relatively small (0.8 points on a 10-point Likert scale). However, use of the CO monitor resulted in a large increase (40% vs. 4%) in referral to the national Quitline. Use of the Quitline typically increases the chance of smoking cessation by 10 times the baseline rate, suggesting that this finding might be clinically important. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.